Alocação de Auto-estrutura utilizando Controle Robusto LQG/LTR e Computação Evolutiva - Ferreira, Carlos Cesar Teixeira (2004)
This work presents a proposal for Eigenstructure Assignment in dynamic stochastic multivariable systems, using LQG/LTR Robust Controllers and Evolutionary Computation. It shows the importance and influence of the Eigenstructure Assignment on the systems dynamic response. It solves the Eigenstructure Assignment problem of the control problem through Linear Quadratic Regulator Design and Genetic Algorithm, developed to perform the search of the state and control weighting matrices in order to assign the Eigenstructure. The Eigenstructure Assignment problem of stochastic state estimation is formulated and solved by using Kalman Filter Design and Genetic Algorithm, now developed to search the state disturbance and measurement noise covariances matrices in order to find an adequate estimator. The Eigenstructure Assignment problem for the stochastic multivariable control with observer is formulated as LQG/LTR Robust Control problem with Loop Transfer Recovery at the Input. This proposal for Eigenstructure Assignment using LQG/LTR Controllers is examined on dynamical system model that representing an aircraft.